2c-3(c-5)=4(2c+1)-3c

Simple and best practice solution for 2c-3(c-5)=4(2c+1)-3c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2c-3(c-5)=4(2c+1)-3c equation:


Simplifying
2c + -3(c + -5) = 4(2c + 1) + -3c

Reorder the terms:
2c + -3(-5 + c) = 4(2c + 1) + -3c
2c + (-5 * -3 + c * -3) = 4(2c + 1) + -3c
2c + (15 + -3c) = 4(2c + 1) + -3c

Reorder the terms:
15 + 2c + -3c = 4(2c + 1) + -3c

Combine like terms: 2c + -3c = -1c
15 + -1c = 4(2c + 1) + -3c

Reorder the terms:
15 + -1c = 4(1 + 2c) + -3c
15 + -1c = (1 * 4 + 2c * 4) + -3c
15 + -1c = (4 + 8c) + -3c

Combine like terms: 8c + -3c = 5c
15 + -1c = 4 + 5c

Solving
15 + -1c = 4 + 5c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-5c' to each side of the equation.
15 + -1c + -5c = 4 + 5c + -5c

Combine like terms: -1c + -5c = -6c
15 + -6c = 4 + 5c + -5c

Combine like terms: 5c + -5c = 0
15 + -6c = 4 + 0
15 + -6c = 4

Add '-15' to each side of the equation.
15 + -15 + -6c = 4 + -15

Combine like terms: 15 + -15 = 0
0 + -6c = 4 + -15
-6c = 4 + -15

Combine like terms: 4 + -15 = -11
-6c = -11

Divide each side by '-6'.
c = 1.833333333

Simplifying
c = 1.833333333

See similar equations:

| 3m^2=6m | | A=1-2(.050)-.020 | | -4(12y)= | | A=1-2(.05)-20 | | -5-12=8x+16-7x | | z^2+4z=21+z-3 | | 4(k-4)-8(k+4)=5(3k-4)-9(3k+4) | | A=1-2(50)-20 | | 3x^2+6x+5x^2-20y-13=0 | | 4b-4-7b-6= | | (2x-1)(2x^3-50x)=0 | | 8x^2-5x=9 | | -1+5=m-7 | | x(3+5)2= | | 2m^2=m^2+36 | | 41y=8(5y-6) | | 12x^2=36 | | y^2-2y-8=0 | | x^2-63=9x | | 8x^2=-5x-9 | | -3(7d+6)= | | X^2+2x+y^2+14y-31=0 | | 7-(3y-4)= | | 2x-8x+6x-3x= | | 5m=12m-30 | | x^2-0.1x-0.02=0 | | 3(3x-2)=10x | | 16x^2-96x-9y^2+36y-36=0 | | 6x^2+4x-2=0 | | 3.15x-3=0.3x^2 | | 4n^2=-12n-2 | | x^5-x=0 |

Equations solver categories